Does higher access ensure greater wellbeing? ‒ In the perspective of forest ecosystem services of the Sundarbans mangrove forest, Bangladesh. (1st July 2019) - Kibria, Abu S.M.G.; Costanza, Robert; Groves, Colin; Behie, Alison M.
Abstract: This study presents the effects of access to Ecosystem Services (ESS) on human wellbeing. In order to fulfil the research objective, we interviewed villagers from 104 households who were exclusively engaged in collecting ESS. Data were also collected from key informants, local leaders, and official records. Higher access (HA) to ESS significantly increased the availability of cleaner water for domestic non-drinking purposes. Access to sufficient food, however, was significantly lower across the HA households because of greater involvement in ESS collection. Overall, in this society, HA families enjoyed significantly greater freedom than Lower access (LA) families. Increased competition for ESS extraction resulting from higher access significantly reduced a collector's physical strength and had larger negative impacts on their mental health (self-esteem decreased and anger level increased) compared to LA collector. There were also significantly stronger financial conditions in the HA families than LA families. Greater access encouraged frequent collaboration and cooperation between HA collectors for collecting more ESS leading to a significant enhancement in social cohesion in compare to LA families. Composite wellbeing scores of the respective wellbeing criteria show that only physical health and economic security would significantly improve with greater access to ESS collection. Thus, ESS can have significant impacts on human wellbeing. However, without integration of other wellbeing improvement programs, sole dependency on the ecosystems would cause resource degradation. These results would greatly assist to improve the current framework of ESS and human wellbeing. Highlights: Higher access (HA) to Ecosystem Services (ESS) increased the availability of cleaner water for non-drinking domestic uses. HA to ESS reduced food sufficiency of the families. HA to ESS enhanced social freedom of the household members. Poorer physical strength and mental health were caused by HA to ESS. Due to HA to ESS financial security and social cohesion were enhanced.